2014
DOI: 10.1177/0267659114525218
|View full text |Cite
|
Sign up to set email alerts
|

Intra-aortic balloon pump (IABP) counterpulsation improves cerebral perfusion in patients with decreased left ventricular function

Abstract: IABP improves cerebral blood flow, particularly in patients with pre-existing heart failure and highly impaired LVEF. Hence, an IABP might be a treatment option to improve cerebral perfusion in selected patients with cerebral misperfusion and simultaneously existing severe heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 32 publications
1
19
0
3
Order By: Relevance
“…Overall, cerebral perfusion relates to CO and blood pressure and to their distinct effects on cerebral haemodynamics [29]. Therefore, enhancement of cardiac performance and optimization of fluid balance, could improve brain perfusion especially in patients with impaired cardiac function [30,31]. Infusion of osmotic therapies -mannitol and HTS -promote a water shift from intracellular to the extracellular (and thus intravascular) compartments and direct peripheral vasodilation, ultimately leading to CO augmentation [3,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, cerebral perfusion relates to CO and blood pressure and to their distinct effects on cerebral haemodynamics [29]. Therefore, enhancement of cardiac performance and optimization of fluid balance, could improve brain perfusion especially in patients with impaired cardiac function [30,31]. Infusion of osmotic therapies -mannitol and HTS -promote a water shift from intracellular to the extracellular (and thus intravascular) compartments and direct peripheral vasodilation, ultimately leading to CO augmentation [3,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Another popular condition for this form of treatment is high-risk that patients are undergoing artery bypass grafting surgery. Treatment using the IABP for patients with severe heart failure showed an increase in cerebral blood flow by 20% augmentation [18]. This increase in blood flow is thought to be an indirect result of the IABP, due to the displacement of blood volume, leading to an increase in coronary flow.…”
Section: Iabp Architecture and Indicationsmentioning
confidence: 99%
“…This increase in blood flow is thought to be an indirect result of the IABP, due to the displacement of blood volume, leading to an increase in coronary flow. For patients that suffer from ischemic stroke, a decrease in left ventricular afterload and increase in cerebral perfusion can be beneficial, which is one reason physicians use the IABP as a form of treatment [18]. Research has also shown that the pump can be used in patients who have undergone a transplant, by normalizing reduced cerebral blood flow.…”
Section: Iabp Architecture and Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Згідно з даними літератури, ВАБК покращує церебральний кровотік. Pfluecke et al у своїй статті показали, що застосування ВАБК підвищив мозковий кровотік на 20 %, при цьому найбільший ефект спостерігався у пацієнтів зі значно зниженою функцією ЛШ [7]. Це може пояснюватись як прямим впливом ВАБК, а саме зміщенням об'єму крові ретроградно під час діастоли в сонні артерії, так і опосередкованимвнаслідок підвищення серцевого викиду через покращання коронарного кровотоку.…”
Section: вступunclassified